Kenyans’ Perceptions of the Risks of COVID-19 Vaccines: A Scoping Review - Faith Anyango Ochieng’; Donal O'Mathuna (Pan-African Journal of Health and Environmental Science)
Background: Vaccination programs are critical in controlling the spread of viral diseases worldwide. The COVID-19 pandemic underscored the critical role of vaccines. Achieving widespread immunization is significantly challenged by vaccine hesitancy, particularly concerns regarding potential risks. The perceptions of Kenyans regarding the risks of COVID-19 vaccines were explored in this scoping review.